Study on operation status of SCR denitration system in Chinese coal-fired power plants. Issue 1 (March 2020) - Zhang, Yang; Feng, Qianwei; Li, Sha; Xu, Ketao; Pei, Yukun; Zhu, Yue
Abstract: Since the beginning of the 12th Five-Year Plan, coal-fired power plants have carried out large-scale denitration and ultra-low emission transformation in China, among which SCR denitration technology is the most widely used. However, some hidden problems in the process of project implementation have gradually emerged after operation due to various factors, such as the centralized reconstruction task, lack of technical experience, inadequate quality control of main equipment, uneven quality of denitration catalysts, and insufficient operation and maintenance experience of power generation enterprises. In this context, the future direction of SCR denitration operation and maintenance management is proposed after a systematic summarization and analysis of the operation status of SCR denitration system in recent years to provide reference for subsequent work.